Analisis Dampak Biaya dan Profitabilitas dari Penerapan Activity-Based Management (ABM) pada PT. Tujuh Konversi Digital - Susiana, R Apria (JURNAL TERAPAN MANAJEMEN DAN BISNIS, 2025)
This research analyzes the financial impact of implementing Activity Based Management (ABM) at PT. Tujuh Konversi Digital, a digital marketing agency in Indonesia. The study aims to evaluate how ABM improves cost efficiency, profitability, and operational communication. Using a descriptive quantitative approach, the research identifies non-value-added activities such as unstructured revisions, excessive meetings, and repeated content reviews that contribute to operational inefficiencies. By applying ABM, the company initiated strategic changes including revision limits in MoUs, monthly client meetings, and the dissolution of the Content Marketing Review (CMR) division. The results reveal that ABM implementation significantly reduced fixed costs by 50% and freelancer expenses by 80%. These cost savings directly contributed to a 115% increase in profitability. Moreover, the restructuring enhanced accountability across departments, streamlined workflows, and improved communication by eliminating bureaucratic barriers. Meetings became more focused, and teams could deliver outputs faster and more accurately. Overall, ABM enabled PT. Tujuh Konversi Digital to offer more competitive services, maintain high-quality standards, and strengthen its market position. This study demonstrates the practical effectiveness of ABM in service-based companies seeking sustainable growth through financial and operational optimization.